تدريس التراكيب النحوية في تعليم اللغة العربية لغير الناطقين بها (دراسة وصفية تحليلية على كتاب "العربية بين يديك" للمجلد الأول) - Ronny Mahmuddin (البصيرة: مجلة الدراسات الإسلامية, 2023)
This research aims to describe the teaching of the structure of nahwu science from the textbook "Al-Arabiyah Baina Yadaika Fi Ta'lim al-Lugah al-Arabiyyah li Ghairi al-Natiqina biha, Volume 1". This type of research is qualitative descriptive research using library methods by conducting content analysis in the textbook "Al-Arabiyyah Baina Yadaika Volume 1" by tracing various references in data collection and analysis. The results of this research show that the textbook "Al-Arabiyyah Baina Yadaika Volume 1" is a textbook that has advantages in teaching the structure of nahwu science in teaching Arabic for non-Arabs. The advantages of this textbook in teaching the structure of Nahwu science can be seen in the following ways. First, this textbook uses patterned and semi-patterned linguistic exercises, namely exercises that aim to create habits and understanding of meaning for students. Second, this textbook uses a variety of intensive linguistic exercises, such as: a) Tadrib al-Hiwar, ask and answer each other as an example; b) Tadrib al-Tahwil, change it as an example; c) Tadrib Takwin al-Jumlah, make sentences as follows; d) Tadrib al-Sual, ask as an example; and e) Tadrib Tartib al-Jumlah, arrange the following sentences. Third, this textbook teaches the structure of Nahwu science and provides a summary of the structure of each new lesson.